The 2019 General Election and the Transparency Question in Nigeria: Political Party Financing As the Bane of Youth Participation - O Babayo Sule; Usman Sambo; Yoserizal Saragih (Britain International for Academic Research (BIAR) Publisher, 2021)
Election is perceived as the most peaceful means of power transfer in a democratic setting. It enables for competitive struggles to secure power in a prescribed rule of the game constitutionally. Nigeria is a democratic state currently undergoing its longest democratic transition unprecedented in the history of the country where six consecutive uninterrupted General Elections were conducted. However, the major issue of concern with Nigeria’s democratisation is youth participation and exclusion from politics. A major factor behind the marginalisation of youth is linked to the transparency question in terms of party financing and money politics. This study examined critically how the process of party financing excluded Nigeria’s youth from participating in the 2019 General Election. The study used a qualitative case study method. Data were gathered from primary and secondary sources. The primary sources included an in-depth interview with relevant stakeholders in the field, direct participant observation and consultation of government’s primary documents. The secondary sources were books, journals, newspapers, reports from organisations and agencies and internet sources. The data collected were discussed and interpreted using statistical techniques of tables, charts and a model. The work discovered that youth were barred from participating in Nigeria’s 2019 General Election in terms of contesting and winning of elective seats emanating from heavy use of money in party financing and campaign expenditure. The study thus, recommends that the viable alternative for youth to participate in Nigerian politics actively is to establish parties and lower the cost of obtaining party nomination and contest.